2018
DOI: 10.1007/s10936-018-9602-7
|View full text |Cite
|
Sign up to set email alerts
|

Perspective-Taking in Referential Communication: Does Stimulated Attention to Addressees’ Perspective Influence Speakers’ Reference Production?

Abstract: In two experiments, we investigated whether speakers' referential communication benefits from an explicit focus on addressees' perspective. Dyads took part in a referential communication game and were allocated to one of three experimental settings. Each of these settings elicited a different perspective mind-set (baseline, self-focus, other-focus). In the two perspective settings, speakers were explicitly instructed to regard their addressees' (other-focus) or their own (self-focus) perspective before constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 60 publications
2
8
0
Order By: Relevance
“…In this sense, explicit instructions to focus their attention on another person’s perspective did not help perceivers to inhibit their privileged perspective to increase their perspective-taking accuracy. These findings by Damen et al (2020) are in line with related studies ( Damen, van Amelsvoort, et al, 2019 ; Damen, van der Wijst, et al, 2019 ), evidencing that an explicit focus on or an explicit awareness of another person’s different perspective does not suffice to reduce perceivers’ tendency to overrely on their own knowledge and attentional status during perspective-taking. It is therefore still unknown how perceivers can be stimulated to sufficiently adjust the self-perspective.…”
Section: Introductionsupporting
confidence: 87%
“…In this sense, explicit instructions to focus their attention on another person’s perspective did not help perceivers to inhibit their privileged perspective to increase their perspective-taking accuracy. These findings by Damen et al (2020) are in line with related studies ( Damen, van Amelsvoort, et al, 2019 ; Damen, van der Wijst, et al, 2019 ), evidencing that an explicit focus on or an explicit awareness of another person’s different perspective does not suffice to reduce perceivers’ tendency to overrely on their own knowledge and attentional status during perspective-taking. It is therefore still unknown how perceivers can be stimulated to sufficiently adjust the self-perspective.…”
Section: Introductionsupporting
confidence: 87%
“…Perspective-taking can be considered to be a vital process for social functioning (Davis, 1983). Ample research has shown, however, that perceivers of other minds often fail to appreciate the other’s different vantage point, even when the social context requires them to do so (Damen, van der Wijst, van Amelsvoort, & Krahmer, 2019; Wardlow Lane, Groisman, & Ferreira, 2006). The question whether and under what circumstances perceivers are able to successfully infer what is going on in the mind of others has received great scholarly attention.…”
mentioning
confidence: 99%
“…The authors concluded that visual salience effects were due to adjustments that speakers make when they speak to an addressee. [41] did not find such adjustment to the addressee. Using a referential communication task, they showed that giving an explicit focus on addressee’s perspective did not influence reference production of the speaker.…”
Section: Discussionmentioning
confidence: 99%